Are teachers willing to educate about death in Chile? - Zamora Poblete, Guillermo; Ow González, Maili; Lecaros Besa, Catalina (Revista Complutense de Educación, 2024)
The purpose of this study is to examine teachers’ views on death education and personal attitudes towards dying. The study also examines the relationship between both dimensions. Two instruments are applied to a sample of 168 primary and secondary school teachers who work in schools in Santiago de Chile. The results indicate that teachers consider that educating about death is a highly relevant topic for their establishments. However, teachers tend to show greater discomfort and resistance to address this issue with their own students. The teachers present feelings of fear and personal avoidance in the face of dying. The study concludes that to promote education about death, a learning community and teacher training are required that reflect on their own deaths, respecting the different experiences and attitudes towards dying.